2019
DOI: 10.1073/pnas.1819971116
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics of Arabidopsis Highly ABA-Induced1 identifies AT-Hook–Like10 phosphorylation required for stress growth regulation

Abstract: The clade A protein phosphatase 2C Highly ABA-Induced 1 (HAI1) plays an important role in stress signaling, yet little information is available on HAI1-regulated phosphoproteins. Quantitative phosphoproteomics identified phosphopeptides of increased abundance inhai1-2in unstressed plants and in plants exposed to low-water potential (drought) stress. The identity and localization of the phosphoproteins as well as enrichment of specific phosphorylation motifs indicated that these phosphorylation sites may be reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 62 publications
7
73
0
1
Order By: Relevance
“…The complexity of AHL action is further enhanced by feedback loop and phosphorylation controlled interactions with other modulators of gene expression. This was recently reported for AHL10 [15], a plant growth modulator under low-water potential stress,…”
Section: Role Of Ahls In Regulation Of Lateral Root Developmentsupporting
confidence: 71%
See 2 more Smart Citations
“…The complexity of AHL action is further enhanced by feedback loop and phosphorylation controlled interactions with other modulators of gene expression. This was recently reported for AHL10 [15], a plant growth modulator under low-water potential stress,…”
Section: Role Of Ahls In Regulation Of Lateral Root Developmentsupporting
confidence: 71%
“…The complexity of AHL action is further enhanced by feedback loop and phosphorylation controlled interactions with other modulators of gene expression. This was recently reported for AHL10 [15], a plant growth modulator under low-water potential stress, affecting jasmonic acid and auxin-synthesis and controlling developmental regulators such as SHOOT MERISTEMLESS (STM) [15].…”
Section: Role Of Ahls In Regulation Of Lateral Root Developmentmentioning
confidence: 62%
See 1 more Smart Citation
“…A recent study showed that the DNA-binding protein AT-Hook-Like 10 (AHL10) could be dephosphorylated by a protein phosphatase Highly ABA-Induced1 (HAI1), which was involved in abiotic stress and abscisic acid signaling. AHL10 phosphorylation was crucial for hormone-related genes during drought stress [44]. Therefore, we thought our candidate gene LOC_Os03g01540 was somehow involved in the ABA signaling pathway to regulate seed dormancy.…”
Section: Candidate Gene Analysismentioning
confidence: 95%
“…Meng et al (2019) revealed jasmonate ZIM-domain protein 7 (JAZ7)-mediated drought tolerance in Arabidopsis using the tandem mass tags (TMT)-based quantitative proteomics and targeted metabolomics. The more advanced proteomics technology, such as quantitative phosphoproteomics are used to elucidate the mechanism that ABAinduced1 identifies AT-Hook-Like10 phosphorylation required for stress growth regulation in Arabidopsis (Wong et al, 2019). Combining comparative transcriptomic and proteomic analyses is also an effective way to investigate differential activation of response and metabolism pathways at the global level (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%